Return To Recurrent Formula In Calculating Definite Integrals - Sherali Abdullayev (Euro Asian Journal Publishing, 2024)
briefly introducing the content of the article, this article covers another convenient way of calculating exact integrals. That is, if the calculation of the exact integral of the sequence is given, then it will be appropriate for us to use recurrent formulas. How is a recurring formula created? You can find the answer to this question by reading the article.
Keywords: integral; definite integral; recurrent sequence